Senior High School Student’s Higher Order Thinking Skill (Hots) In Writing Analytical Exposition Text - Jundullah Faris Mu’Tashim; Faishol Hadi (Journal of English Language Teaching and Islamic Integration, 2021)
The type of research is a descriptive study with a qualitative approach. The research subjects were students in XI MIPA 1 at SMAN 1 Purwosari. The stages of the research include preparation, data collection, data analysis, and report making. The aim of this research to describe student’s higher order thinking skill in writing analytical exposition text. The research instrument used were rubric score of HOTS in writing. The research instrument was a rubric score of HOTS in writing. It was appropriate with the government curriculum about K-13. The research instrument is also based on the real problem. It would help students solve the problem. Because in HOTS, they will try to analyzed the problem. Then, they able evaluate or assess the problem. After that, they able to create a solution. The result explained that subject 3 with high academic report in English lesson able to reach excellent level of HOTS and the others had good level of HOTS. According to this research, students from SMAN 1 Purwosari need appropriate strategies and teaching materials to improve their writing skill in higher order thinking skill